Evidence of sociocultural factors influencing intimate partner violence among young women in sub-Saharan Africa: a scoping review - Maria Suzana Maguele; Myra Taylor; Nelisiwe Khuzwayo (BMJ Open, 2020)
Objective This study carried out a scoping review of research on intimate partner violence to determine the extent to which studies on sociocultural factors influencing intimate partner violence among young women (15–24 years) have been conducted, and how different geographical areas are represented. It also considered whether the methodologies used were sufficient to describe the risk factors, prevalence and health outcomes associated with intimate partner violence among young women. Study design Scoping review. Methods Online databases were used to identify studies published between 2008 and 2019. The Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines by Arksey and O’Malley were used to select studies, and primary studies were assessed using the Mixed Method Appraisal Tool, V.2011. Thematic content analysis was used to summarise the findings of the scoping review. Results The majority of publications eight (61.5%) reported cross-sectional studies, while four (31.5%) were qualitative studies. One of the studies (7%) collected measured data. Overall, 13 (100%) of the publications examined factors influencing intimate partner violence. Using a customised quality assessment instrument, 12 (92.3%) of studies achieved a ‘high’-quality ranking with a score of 100%, and 7.7% of studies achieved an ‘average’ quality ranking with a score of 75%. Conclusions While the quality of the studies is generally high, researches on sociocultural factors influencing intimate partner violence among young women would benefit from a careful selection of methods and reference standards, including direct measures of the violence affecting young women. Prospective cohort studies are required linking early exposure with individual, sociocultural and community factors, and detailing the abuse experienced from childhood, adolescence and youth. PROSPERO registration number CRD42018116463. Scoping protocol publication https://doi.org/10.1186/s13643-019-1234-y